2023
DOI: 10.1021/acs.analchem.3c01968
|View full text |Cite
|
Sign up to set email alerts
|

Integration of CRISPR/Cas13a and V-Shape PCR for Rapid, Sensitive, and Specific Genotyping of CYP2C19 Gene Polymorphisms

Abstract: Rapid detection of single nucleotide polymorphisms (SNPs) in the CYP2C19 gene is of great significance for clopidogrel-accurate medicine. CRISPR/Cas systems have been increasingly used in SNP detection due to their single-nucleotide mismatch specificity. PCR, as a powerful amplification tool, has been incorporated into the CRISPR/Cas system to improve the sensitivity. However, the complicated three-step temperature control of the conventional PCR impeded rapid detection. The “V” shape PCR can shorten about 2/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The discovery of target-activated nonspecific endonuclease activity (also known as trans -cleavage activity) in Cas effectors, particularly Cas12 and Cas13, has sparked great interest in developing novel molecular diagnostic tools for various biomarkers. For a typical Cas13a assay, a specific crRNA guides the Cas enzyme to precisely recognize the target RNA and then activates the trans -cleavage toward surrounding single-stranded RNA reporters, enabling the development of amplification-free sensing platforms. However, the sensitivity of these amplification-free CRISPR/Cas methods is always around the picomolar (pM) level, which cannot meet the requirement of real sample measurement. To improve the detection sensitivity, various nucleic acid amplification technologies, such as PCR, RPA, , and LAMP, have been integrated with the CRISPR/Cas13a system and demonstrated that the combination of amplification technologies can confer the Cas13a-based sensing strategies with ultrahigh sensitivity.…”
mentioning
confidence: 99%
“…The discovery of target-activated nonspecific endonuclease activity (also known as trans -cleavage activity) in Cas effectors, particularly Cas12 and Cas13, has sparked great interest in developing novel molecular diagnostic tools for various biomarkers. For a typical Cas13a assay, a specific crRNA guides the Cas enzyme to precisely recognize the target RNA and then activates the trans -cleavage toward surrounding single-stranded RNA reporters, enabling the development of amplification-free sensing platforms. However, the sensitivity of these amplification-free CRISPR/Cas methods is always around the picomolar (pM) level, which cannot meet the requirement of real sample measurement. To improve the detection sensitivity, various nucleic acid amplification technologies, such as PCR, RPA, , and LAMP, have been integrated with the CRISPR/Cas13a system and demonstrated that the combination of amplification technologies can confer the Cas13a-based sensing strategies with ultrahigh sensitivity.…”
mentioning
confidence: 99%